THE ROLE AND FUNCTIONS OF THE STATE IN THE TRANSFORMATION OF SOCIO-ECONOMIC SYSTEMS - Stativka, N.; Bubliy, M. (Pressing Problems of Public Administration, 2020)
The article examines the role and functions of the state in the transformation of socio-economic systems. It is proved that the process of transformation of the socio-economic system occurs under the influence of both the market trend towards equilibrium and state policy: the state acts as a subject of transformational transformations. The regulatory role of the state in the transformation of the socio-economic system is to implement the necessary reforms, institutional changes, and promote the development of the domestic economy against the background of countering the negative consequences of globalization. The state, influencing the directions of transformation of the socio-economic system, forms a system of development priorities in accordance with the goals of business and the interests of society, as well as restrictions imposed by the national and global economic system. In the course of the study, it was noted that the market mechanism can fail, since the market is not always capable of self-regulation. The reasons for such failures include external effects, the mutual influence of individuals ‘ activities on personal well-being, and the need to create public goods. Three groups of regulatory functions of the state in the transformation of socio-economic systems are defined: functions to create conditions for the effective functioning of the market, functions to stimulate the development of an industrial basis, functions to support the post-industrial sector of the economy, while the common basis for all groups of functions is the formation, transformation and improvement of institutional relations necessary for a highly efficient economy. The functions of the state in the process of transformation of the socio-economic system are characterized by the fact that with the help of legislative, executive and judicial power, the state coordinates and structures the interaction of all elements of the system in the interests of economic entities and social groups. It is found out that the features of state regulation of the transformation of the socio-economic system of Ukraine consist in the fact that it is necessary to solve a wide range of tasks of both catching up and advanced development, using a set of regulatory tools that ensure transformation in given target areas. In this regard, direct and indirect selective regulation with the use of program-target methods when using an institutional approach to innovative transformation of the socio-economic system of Ukraine is promising. The article examines the role and functions of the state in the transformation of socio-economic systems. It is proved that the process of transformation of the socio-economic system occurs under the influence of both the market trend towards equilibrium and state policy: the state acts as a subject of transformational transformations. The regulatory role of the state in the transformation of the socio-economic system is to implement the necessary reforms, institutional changes, and promote the development of the domestic economy against the background of countering the negative consequences of globalization. The state, influencing the directions of transformation of the socio-economic system, forms a system of development priorities in accordance with the goals of business and the interests of society, as well as restrictions imposed by the national and global economic system. In the course of the study, it was noted that the market mechanism can fail, since the market is not always capable of self-regulation. The reasons for such failures include external effects, the mutual influence of individuals ‘ activities on personal well-being, and the need to create public goods. Three groups of regulatory functions of the state in the transformation of socio-economic systems are defined: functions to create conditions for the effective functioning of the market, functions to stimulate the development of an industrial basis, functions to support the post-industrial sector of the economy, while the common basis for all groups of functions is the formation, transformation and improvement of institutional relations necessary for a highly efficient economy. The functions of the state in the process of transformation of the socio-economic system are characterized by the fact that with the help of legislative, executive and judicial power, the state coordinates and structures the interaction of all elements of the system in the interests of economic entities and social groups. It is found out that the features of state regulation of the transformation of the socio-economic system of Ukraine consist in the fact that it is necessary to solve a wide range of tasks of both catching up and advanced development, using a set of regulatory tools that ensure transformation in given target areas. In this regard, direct and indirect selective regulation with the use of program-target methods when using an institutional approach to innovative transformation of the socio-economic system of Ukraine is promising.